Several Geological Issues of Schrödinger Basin Exposed by CE-2 CELMS Data - Z. G. Meng; H. H. Wang; Y. C. Zheng; Y. Z. Wang; H. Miyamoto; Z. C. Cai; J. S. Ping; Y. Z. Zhu (Advances in Astronomy)
The study on the Schrödinger basin may provide important clues about the formation of South Pole-Aitken (SPA) basin. In this paper, the thermophysical features of Schrödinger basin were evaluated using the Chang’E-2 microwave sounder (CELMS) data. The results are as follows. (1) The geological units are reevaluated with the CELMS data and a new geological view was provided according to the brightness temperature and emissivity maps. (2) The surface topography plays an important role in the observed CELMS data. (3) The hot anomaly in the basin floor indicates a warm substrate. (4) The pyroxene-bearing anorthosite is probably an important cause for the cold anomaly over the lunar surface. Also, the study proves the applicability of the CELMS data applying in high latitude regions to a certain extent.